STUDI TENTANG KEPUASAN PENGGUNA “BRT TRANS” DI SEMARANG - Siti Aminah; Achmad Zaenuri (Serat Acitya, 2019)
This study is to examine the effect of rates and facilities on consumer satisfaction who used TRANS BRT Semarang. The population in this passengers who used TRANS BRT in Semarang, its  sample is taken general passengers using convenience sampling and the respondents were taken from  who are passengers currently using BRT TRANS Semarang. Data analysis techniques used in this research is multiple regression analysis techniques. The results show that their rates and facilities significantly influence consumer satisfaction who used TRANS BRT Semarang.Keyword : rates, facilities, student’s satisfaction.